Biosensors for Klebsiella pneumoniae with Molecularly Imprinted Polymer (MIP) Technique - Chuchart Pintavirooj; Naphatsawan Vongmanee; Wannisa Sukjee; Chak Sangma; Sarinporn Visitsattapongse (Sensors, 2022)
, where the sensitivity was 2.634 and 2.226, respectively. Our sensor was also able to achieve a limit of detection (LOD) of 0.012 CFU/mL and limit of quantitation (LOQ) of 1.61 CFU/mL.
Keywords: Biosensors and Analytical Detection; Bacterial biofilms and quorum sensing; Analytical chemistry methods development